A Study of South-West Monsoon Over Indian Sub-Continent using Satellite Derived Precipitation Estimates - Giri Prasad, P.; Varadarajan, S. (International Journal of Engineering and Technology, 2018)
In the present study, an investigation has been made over Indian Sub-Continent during South-West Monsoon for the years 2015-2016. The results show that no precipitation products are close to the gridded actual rainfall. But good correlation coefficients (CC) exist between the satellites derived precipitation product and actual rainfall. In this paper, multisatellite high-resolution precipitation products,namely Climate Prediction Center Morphing (CMORPH) version 1.0, TRMM Multisatellite Precipitation Analysis (TMPA)-3B42 V7 product are compared with India Meteorological Department (IMD) gridded rainguage data.From the results, it is observed that south west monsoon during 2016 produces more rainfall compared to monsoon season of 2015. Five different regions with different climate zones are selected shows the variability of climate over Indian Sub-Continent. For the selected regions, monthly average rainfall(in mm) ,Correlation Coefficient(CC) and Root Mean Square Error (RMSE)Â are evaluated for satellite derived precipitation products and IMD gridded rain guage data.